The ergonomics kit for general industry : with training disc - MacLeod, Dan (Lewis Publishers, 1999)
Offers a comprehensive training program to prevent and curtail ergonomic risk in the workplace, with methods that trainers can use to recognize, evaluate, and control ergonomic-related difficulties